2017
DOI: 10.12688/f1000research.10519.1
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2A randomized, double-blind, placebo-controlled pilot trial of GM604 in patients with Amyotrophic Lateral Sclerosis (ALS Protocol GALS-001) and a single compassionate patient treatment (Protocol GALS-C)

Abstract: Background Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that lacks effective treatment options. Genervon has discovered and developed GM604 (GM6) as a potential ALS therapy. GM6 has been modeled upon an insulin receptor tyrosine kinase binding motoneuronotrophic factor within the developing central nervous system. Methods This was a 2-center phase 2A, randomized, double-blind, placebo-controlled pilot trial with 12 definite ALS patients diagnosed within 2 years of disease onset. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…While multitarget approaches are becoming increasingly popular in drug discovery against multifactorial diseases, their application to ALS therapy has received little attention. The peptidic drug alirinetide (GM604, GM6, l -phenylalanyl- l -seryl- N 5 -(diaminomethylene)- l -ornithyl- l -tyrosyl- l -alanyl- N 5 -(diaminomethylene)- l -ornithine), which was granted fast track status by the FDA and orphan drug designation by the EMA and has undergone phase II clinical trials for the treatment of ALS, is believed to promote neuron survival via a multitargeted regulation of developmental pathways, although it was not designed using the MTDL paradigm. Regarding small molecules, the multitarget iron chelator VAR10303 has shown beneficial effects on ALS mice .…”
Section: Introductionmentioning
confidence: 99%
“…While multitarget approaches are becoming increasingly popular in drug discovery against multifactorial diseases, their application to ALS therapy has received little attention. The peptidic drug alirinetide (GM604, GM6, l -phenylalanyl- l -seryl- N 5 -(diaminomethylene)- l -ornithyl- l -tyrosyl- l -alanyl- N 5 -(diaminomethylene)- l -ornithine), which was granted fast track status by the FDA and orphan drug designation by the EMA and has undergone phase II clinical trials for the treatment of ALS, is believed to promote neuron survival via a multitargeted regulation of developmental pathways, although it was not designed using the MTDL paradigm. Regarding small molecules, the multitarget iron chelator VAR10303 has shown beneficial effects on ALS mice .…”
Section: Introductionmentioning
confidence: 99%
“…No approved treatment significantly extends survival for ALS patients. GM604 has good drug-like properties [ 10 , 17 ] and has demonstrated safety with promising effects in a small phase IIA clinical study [ 18 ]. This study used RNA-seq to provide the first complete analysis of gene expression responses to GM6 using the SH-SY5Y neuroblastoma model.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular uptake of GM6 has been directly demonstrated using quantitative imaging in induced pluripotent stem cell-derived GABAergic neurons, and liver microsome assays further indicated that its clearance rate was unaffected by Riluzole [ 10 ]. Recently, a multi-center phase IIA clinical trial was reported in which outcomes were compared between 8 ALS patients receiving GM6 and 4 patients receiving placebo for a 2 week period (ClinicalTrials.gov identifier: NCT01854294) [ 18 ]. Although findings from this study do not yet demonstrate efficacy, this trial has demonstrated safety in ALS patients with encouraging trends related to ALS Functional Rating Scale (ALSFRS), forced vital capacity, and ALS biomarkers (e.g., TDP-43, tau protein and SOD1) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In several clinical trials, the drug’s impact was determined by comparing the expression of different markers in patients exposed to drugs or placebo (NCT01854294, NCT03800524, NCT04505358, NCT03693781) or observing pre- and post-treatment clinical outcomes (NCT01884571, NCT02525471, NCT02469896, NCT05193994, NCT04788745). Notably, the results of trial NCT01854294 showed that the master regulator peptide GM604 altered plasma expression levels of SOD1, TAU and TDP-43 proteins, slowing down disease progression [ 20 ]. In trial NCT01884571, analysis of mRNA expression profiles in blood T-cells was used to assess the effect of immunosuppression and showed no disease-modifying effect following this treatment [ 21 ].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…A multi-omics approach has been used in trail NCT02590276 to identify disease signatures in FTD/ALS C9Orf72-carriers [ 29 ]. The results implicated dysregulated circulating miRNAs as biomarkers of disease progression [ 20 ]. In trial NCT03984708, analysis of metabolic status and associated metabolic pathways in skin biopsy fibroblasts of ALS patients was used to find new therapeutic strategies.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%